Assessment of the Value of Routine Blood Cultures in the Evaluation and Treatment of Patients With Chorioamnionitis - Gregory J. Locksmith; Patrick Duff (Hindawi Limited, 1994)
Objective: The objective of this investigation was to determine the usefulness of blood cultures in evaluating patients with chorioamnionitis who were treated in accordance with a specific antibiotic protocol.